Multi-criteria feasibility of real use of self-compacting concrete with sustainable aggregate, binder and powder. (20th November 2021) - Revilla-Cuesta, Víctor; Skaf, Marta; Espinosa, Ana B.; Ortega-López, Vanesa
Abstract: Replacing natural raw materials with industrial by-products can increase the sustainability of Self-Compacting Concrete (SCC), although its fresh and hardened behavior will usually worsen. The benefits of increased sustainability must therefore outweigh any reduction in concrete flowability and strength. These aspects can be analyzed through Multi-Criteria Decision-Making (MCDM) algorithms. In all, 19 SCC mixes were studied. One reproduced commercial SCC (limestone filler and conventional cement), the others were produced with more sustainable materials: 100% coarse Recycled Concrete Aggregate (RCA); 0%, 50% or 100% fine RCA; 45% Ground Granulated Blast-furnace Slag (GGBS); and sustainable aggregate powders such as limestone fines 0/0.5 mm and RCA powder 0/0.5 mm. Decreased flowability at 15 and at 60 min, compressive strength, modulus of elasticity, carbon footprint, and cost of mix were all studied. Both the carbon footprint and the cost were calculated considering only the composition of the SCC, without including aspects that depend on each particular case study, such as transport distances. These aspects constituted the decision-making criteria of the MCDM analysis, under which 14 scenarios were evaluated with different requirements for SCC, using 3 different algorithms (TOPSIS, AHP, and PROMETHEE). The results suggested that the ideal choice for fast concreting is a combination of GGBS, 100% coarse RCA and limestone fines, although if SCC has to be transported to the concreting point, then conventional cement should be used. Strength and stiffness can be maximized by limiting the fine RCA content to 50%. Finally, considering a versatile choice, only SCC with coarse RCA, limestone fines, GGBS and 0% fine RCA could compete with conventional SCC. Adapting the design to minimize the detrimental effects of by-products is therefore essential to promote sustainable SCC that is also commercially competitive. Graphical abstract: Image 1 Highlights: 19 SCC mixes made with GGBS, recycled aggregates and sustainable aggregate powder. Comprehensive MCDM analysis with 3 algorithms and 14 scenarios of evaluation. GGBS only advisable if maximizing short-term flowability and strength. Limestone fines improved SCC sustainability and behavior versus conventional filler. Behavior-focused design essential to get green SCC competitive with commercial SCC.